The Effectiveness of Powtoon Audio-Visual Media-based PBL on Historical Learning Motivation - Yosie Eva Purbaningrum; Aman Aman (STAI Hubbulwathan Duri, 2023)
The subject of history is often considered uninteresting due to its extensive content and traditional teaching methods. Consequently, students tend to lose motivation and enthusiasm towards the subject. Therefore, teachers are required to adopt creative teaching approaches, such as using learning media and implementing engaging teaching strategies. Hence, this study aimed to examine the influence of problem-based learning-based PowToon audio-visual media on the learning motivation of 7th-grade students regarding history at MTs Pamulangan. The study employed an experimental research approach using the Posttest-Only Control Design with 33 seventh-grade students randomly selected as the research sample. Data were collected using questionnaires to measure research variables. The effectiveness of problem-based learning audio-visual PowToon media on students' motivation to learn history was analyzed using the t-test via a paired sample t-test, preceded by normality and homogeneity tests. The results showed that students in the experimental class who received the treatment exhibited a higher motivation level (average of 66.13) than those in the control class who did not use PBL-based PowToon media (average of 61.52). Furthermore, students showed a greater interest in learning history when utilizing PBL-based PowToon media, as evidenced by the t-count value of 2.034, exceeding the t-table value of 1.68. Therefore, H0 was rejected, and H1 was accepted. In conclusion, a significant difference was observed between the average history learning motivation of the experimental and control classes.